Development Of Invertebrate Instruments To Improve Critical Thinking - Berlian, Mery; Devionita, Dheanda; Yuliastrin, Adisti; Yusra, Nelly; Vebrianto, Rian (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
Research instruments are tools used to collect research data, both qualitative and quantitative data. Qualitative data can be in the form images, words, and/or other objects that are non-numerical, while quantitative data is data that is or is in the form of numbers. This research was used as an assessment test to measure students' critical thinking in junior high school, specifically invertebrate material. For students, assessment instruments function as a means of evaluating their understanding of the material taught by the teacher. Therefore, teachers need to develop assessment instruments that can stimulate students to develop critical thinking skills. This research uses the RND method with the ADDIE model. Five descriptive questions will be developed, each reflecting an indicator of critical thinking skills which serves as a guide in making test instruments. The five indicators of critical thinking skills and the detailed questions that represent them. This test assessment instrument was tested on 40 individuals using validity and reliability tests, including students, prospective teachers and teachers.The research results show that this instrument can be used and is declared valid with a validity value of 81.11% and is declared valid, while for reliability it gets a score above 0.6 which is categorized as reliable and Critical thinking test assessment instruments on invertebrate material can be used by teachers.